Higher Quality, Lower Cost with an Innovative Geriatrics Consultation Service. Issue 9 (10th August 2018) - Bernstein, Juliana M.; Graven, Peter; Drago, Kathleen; Dobbertin, Konrad; Eckstrom, Elizabeth
Abstract : Objectives: To design a value‐driven, interprofessional inpatient geriatric consultation program coordinated with systems‐level changes and studied outcomes and costs. Design: Propensity‐matched case–control study of older adults hospitalized at an academic medical center (AMC) who did or did not receive geriatric consultation. Setting: Single tertiary‐care AMC in Portland, Oregon. Participants: Adults aged 70 and older who received an inpatient geriatric consultation (n=464) and propensity‐matched controls admitted before development of the consultation program (n=2, 381). Pre‐ and postintervention controls were also incorporated into cost difference‐in‐difference analyses. Measurements: Daily charges, total charges, length of stay (LOS), 30‐day readmission, intensive care unit (ICU) days, Foley catheter days, total medication doses per day, high‐risk medication doses per day, advance directive and Physician Orders for Life Sustaining Treatment (POLST) documentation, restraint orders, discharge to home, and mortality. Results: On average, individuals who received a geriatric consultation had $611 lower charges per day than those without a consultation (p=.02). They spent on average 0.36 fewer days in the ICU (p<.001). They were less likely to have restraint orders (20.0% vs 27.9%, p<0.001), more likely to have a POLST (58.2% vs 44.6%, p<.001), and more likely to be discharged to home (33.4% vs 28.2%, p=.03). They received fewer doses of antipsychotics, benzodiazepines, and antiemetics (10, 5, and 7 fewer doses per 100 patient‐days, respectively) and had lower in‐hospital mortality (2.4% vs 4%, p=.01). There was no difference in hospital LOS or 30‐day readmission. Conclusion: Our consultation program resulted in significant reductions in daily charges, ICU days, potentially inappropriate medication use, and use of physical restraints and increased end‐of‐life planning. This model has potential for dissemination to other institutions operating in resource‐scarce, value‐driven settings.